(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
This study was conducted in six sacred sites located in Lattakia governorate during the period between 2020-2021, This study showed that the sacred sites in the countryside had more species richness especially in natural plant species compared to sacred sites in the city with less species richness which is considered the most rich with exotic species. this study was showed that a discrepancy between the sacred sites in the city and the countryside, which percentage of exotic species in the city %60 and the countryside 10.2%, while the natural species were recorded a percentage of 40 % in the city compared to 89.79% in the countryside. The similarity between the city and the countryside was 22.38%. Fabales order had the first digree according to their appearance in sacred sites in both the city and the countryside by 12.12%, then Sapindales order 9.09%, whereas Lamiales gave 7.57%, while Asteraceae, Lamiaceae and Cupressaceae families had the first digree by 6.06%.